New records of parasitic copepods (Crustacea, Copepoda) from marine fishes in the Argentinean Sea - Cantatore, Delfina María Paula (2012)
Increasing knowledge of the biodiversity of parasitic copepods in the Argentinean Sea will provide a baseline against which changes in the distribution of marine biota can be detected. We provide new information on the distribution of 13 known species of parasitic copepods gathered from 11 species of marine fishes from Argentinean Sea, including 7 new host records and 9 new locality records. These species are: Bomolochus globiceps (Vervoort et Ramírez, 1968) and Nothobomolochus cresseyi Timi et Sardella, 1997 (Bomolochidae Sumpf, 1871); Brasilochondria riograndensis Thatcher et Pereira, 2004 (Chondracanthidae Milne Edwards, 1840); Taeniacanthus lagocephali Pearse, 1952 ( Wilson, 1911); Caligus rogercresseyi Boxshall et Bravo, 2000 and Metacaligus uruguayensis (Thomsen, 1949) (Caligidae Burmeister, 1835); Hatschekia conifera Yamaguti, 1939 (Hatschekiidae Kabata, 1979); Clavellotis pagri (Krøyer, 1863), Clavella adunca (Strøm, 1762), Clavella bowmani Kabata, 1963 and Parabrachiella amphipacifica Ho, 1982 (Lernaeopodidae Milne Edwards, 1840), and Lernanthropus leidyiWilson, 1922 and Lernanthropus caudatus Wilson, 1922 (Lernanthropidae Kabata, 1979). A list of host species lacking parasitic copepods, for which large samples were investigated by the authors, is also provided in order to compare in future surveys.